PHARMACOLOGICAL EVALUATION OF MORINGA OLEIFERA LEAF EXTRACT FOR ANTIDEPRESSANT ACTIVITY: A REVIEW - Jagdish Abadar, Vaishnavi Adkine, Nikita Ambhore, Shinde Punam (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The prevalence of mental depression has increased in recent years, and has become a serious health problem in most countries of the world, including India. Due to the high cost of antidepressant synthetic drugs and their accompanying side effects, the discovery of safer antidepressant herbal remedies is on the rise .This work was carried out to antidepressant effect of n-hexane fraction of Moringa oleifera. Depression is a neurological disorder characterized by apathy, loss of energy, decreased mood, feeling of guilt, loss of interest, retardation of thinking and activity as well as profound feelings of gloominess, despair and suicidal ideation. About 21% of the world population is largely affected by depression. Many people in the world advocate the use of Moringa oleifera to treatvariety of central nervous system illnesses. Moringa oleifera (MO) (drumstick) has been used in traditional old medicine, and in Ayurveda, it is considered as a valuable remedy for treating nervous system disorders as well as memory enhancing agent. The present study was undertaken to investigate the effect of ethanolic extract of moringa oleifera in mice. In the present study, the antidepressant effect of moringa oleifera was examined using two behavioural models, the forced swimming test (FST) and tail suspension test (TST). Depression is a wide spread psychiatric disorder. According to WHO, 450 million people suffer from a mental or behavioural disorder. this amount to 12.3% of global burden of disease and predicted to rise upto 15% by 2020. In traditional system of medicine, many plants and formulation have been used to treat depression for thousands of years. moringa oleifera is known miracle tree its every part having medicinal use for human. The present study reports physicochemical characterization, antidepressant activity of extracts from Moringa Oleifera leaves collected from local region of Nanded, Maharashtra, and India. The In-Vivo antidepressant activity of Moringa Oleifera leaf was evaluated by forced swim test model in mice using imipramine as a standard.